Implementasi Metode Pembiasaan Dalam Membangun Karakter Religius Pada Anak Usia 4-5 Tahun Di Paud Nurul Ikhlas Padarincang - Zulfi Aali Dawwas, Ahmad; Alivianti, Mutia; Samudi; Kurnia, Lita (E-JURNAL AKSIOMA AL-ASAS, 2025)
The purpose of this study was to determine how the implementation of the habituation method is in PAUD Nurul Ikhlas Padarincang and to determine the results of the implementation of the habituation method in improving religious character in early childhood in PAUD Nurul Ikhlas Padarincang. Religious character is a character that refers to attitudes and behaviors that reflect religious values in everyday life. Seeing how important the religious character can be developed by teachers by introducing religious character that is applied through the habituation method in daily activities.This study uses a descriptive qualitative method with a case study type analyzing data according to written facts and presenting it by making one class A teacher as the subject/data source. Then the data collection tools used by the author are observation, interviews and documentation.The results of this study can be found by the author that teachers in improving children's religious character through good behavior habits, namely through routine and spontaneous habits. The routine habituation is the habit of reading prayers before and after studying and reading prayers before and after eating, spontaneous habituation that is done is spontaneously saying and answering greetings and being polite to teachers and friends. Then the results of the implementation of the habituation method that the teacher does can improve the religious character of children in group A PAUD Nurul Ikhlas Padarincang. This is in accordance with the results of a child study where the four indicators studied on 12 children in group A reached a class average of 56% with 6 children developing very well and 6 children developing according to expectations.